Unsaponifiable matter from oil of green coffee beans: cosmetic properties and safety evaluation. (2nd October 2016) - Wagemaker, Tais A. L.; Campos, Patrícia M. B. G. Maia; Fernandes, Ana Sofia; Rijo, Patrícia; Nicolai, Marisa; Roberto, Amílcar; Rosado, Catarina; Reis, Catarina; Rodrigues, Luis M.; Carvalho, Cássia Regina Limonta; Maia, Nilson Borlina; Guerreiro Filho, Oliveiro
Abstract: Context: Unsaponifiable matter (UM), a fraction of green coffee oil (GCO) contains functional compounds responsible for desirable cosmetic properties such as UV-B absorption. Objectives: To evaluate oil content and sun protection factor (SPF) variability of the two most important species of coffee and, the toxic and cytotoxic effects, as well as cosmetic properties, including antioxidant and antimicrobial activities of UM obtained from green Coffea arabica seed oil. Materials and methods: The safety and potential cosmetic properties of UM extracted from green coffee oil (GCO) were evaluated by the brine shrimp viability and the MTT cytotoxicity assays. The SPF and antioxidant activity were evaluated using in vitro methods. Results: Relevant cytotoxicity was found against keratinocytes for concentrations ≥25 µg/mL and in the brine shrimp assay (LC50 24 µg/mL). Antimicrobial and antioxidant activities (IC50 1448 µg/mL) were low in UM but SPF was 10 times higher than in GCO. Conclusion: UM is a novel potential UV-B absorbent but its use as a cosmetic ingredient should be better considered due to the considerable cytotoxicity shown in the experimental conditions described.